2016
DOI: 10.25011/cim.v39i6.27511
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ginkgo biloba extract on brain oxidative condition after cisplatin exposure

Abstract: Effects of Ginkgo biloba extract on brain oxidative condition after cisplatin exposure Abstract Purpose: The purpose of this study was to evaluate the efficacy of Ginkgo biloba extract (EGb 761) on oxidative events of brain in cisplatin-administrated rats.Methods: Rats were divided into four experimental groups: 1) control (n=6); 2) cisplatin (8 mg/kg, intraperitoneally one dose, n=6); 3) EGb 761 (100 mg/kg intraperitoneally for 15 days, n=6); and 4) cisplatin + EGb 761 (n=6). After drug administration, rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
5
5
0
Order By: Relevance
“…This hypothesis was further confirmed in the present study by the enhanced level of MDA (the end product of LPO) and PC (a reliable indicator for protein oxidation) in the brain. These results are in agreement with earlier reports 20,39. NO is a strong damaging free radical when produced in excess.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This hypothesis was further confirmed in the present study by the enhanced level of MDA (the end product of LPO) and PC (a reliable indicator for protein oxidation) in the brain. These results are in agreement with earlier reports 20,39. NO is a strong damaging free radical when produced in excess.…”
Section: Discussionsupporting
confidence: 94%
“…The involvement of NO in the toxicity of CDDP has been reported and was attributed to the enhancement of inducible NO syn-thase 40. Results from our study showed a marked increase in NO level in the brain of CDDP-administered rats which agrees with Aydin et al20 CDDP-induced changes in MDA, PC, and NO levels were significantly alleviated with NAC treatment. The ameliorative effect of NAC may be largely attributed to its ability to eradicate free radicals.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The primary evidence of neurotoxicity of cisplatin is decreased activity of antioxidant enzymes with concomitant depletion in the glutathione level, elevated lipid membrane peroxidation, and mitochondrial dysfunction. This indicates that cisplatin causes overproduction of ROS and imbalance between oxidant-antioxidant levels, consequently leading to the insufficient level of antioxidants to counteract the raised ROS in tissue [3]. Besides, cisplatin-induced neurotoxicity has been shown to result in numerous clinical forms.…”
Section: Introductionmentioning
confidence: 99%
“…EGb 761 could be protective against ischemic injury by regulating oxidative stress. Aydin D induced oxidation in rat brains by administering cisplatin and found that EGb 761 could decrease the level of NO and GSH in brain tissue, thereby reducing oxidative stress[ 17 ]. Similarly, EGb 761 possessed the ability to reverse the decrease in GSH and GSH-peroxidase levels induced by intermittent hypoxia in rats [ 18 ].…”
Section: Pharmacological Actions Of Egbmentioning
confidence: 99%